Pembekalan Learning How To Learn Bahasa Inggris Untuk Mahasiswa Se-Kota Mataram Dalam Menunjang Pencapaian Indikator Kerja Utama (IKU) - Eka Fitriana; L. Muhaimi; Kurniawan Apgrianto; Desi Herayana (Universitas Mataram, 2023)
The role of the English is becoming increasingly crucial for students and other members of the community with the issuance of the Regulation on Key Performance Indicators (IKU) as a reflection of the success of a higher education institution in implementing the three pillars of higher education. English is needed to support IKU 1, which aims to produce graduates who can meet the qualifications needed by the workforce and those who advance their studies to a higher level, demanding English proficiency. Meanwhile, IKU 3 requires good oral and written communication skills so that students can intern in large and reliable companies within the Work-Integrated Learning (WIL) program. Another important demand is that the English proficiency is one of the indicators for students to be competitive internationally. However, this significant demand is not in line with the English language proficiency of students enrolled in state and private universities in the city of Mataram, many of whom are still at the basic and elementary levels. The purpose of this Community Service (PkM) is to enhance the knowledge and English skills of students with a focus on learning how to learn. The activity involves a tutoring session covering the basic concepts of learning how to learn, the learning process, learner autonomy in learning, and concludes with a Focus Group Discussion (FGD). The activity is led by a team of four Community Service Program members from the English Education Department at the University of Mataram. The activity takes place at the Mataram Lingua Franca Institute (Malfi) as the collaborating partner. Twenty participants from various state and private universities in the city of Mataram are involved in this PkM.